Centromere Repeat DNA Originated from Brassica rapa is Detected in the Centromere Region of Raphanus sativus Chromosomes - Hwang, Y.J., Kyungpook National University, Daegu, Republic of Korea; Yu, H.J., The Catholic University of Korea, Bucheon, Republic of Korea; Mun, J.H., National Academy of Agricultural Science, RDA, Suwon, Republic of Korea; Ryu, K.B., Kyungpook National University, Daegu, Republic of Korea; Park, B.S., National Academy of Agricultural Science, RDA, Suwon, Republic of Korea; Lim, K.B., Kyungpook National University, Daegu, Republic of Korea (Weon'ye gwahag gi'sulji, 2012)
Fluorescence in situ hybridization (FISH) is a powerful tool for the detection of DNA sequences in the specific region of the chromosomes. As well as for the integrated physical mapping, FISH karyotype analysis has to be preceded. Karyotype of Raphanus sativus 'Wonkyo 10039' was analyzed by a dual-color FISH technique; using various repetitive DNA probes, including 5S rDNA, 45S rDNA, and centromere retrotransposon. The length of the somatic metaphase chromosome ranged from 1.35 to 2.06 ㎛ with a total length of 15.29 ㎛. The chromosome complements comprised of eight pairs of metacentrics and one pair of submetacentric. Bleached DAPI Band analysis revealed a heterochromatin region, covering 28.6% to 50.4% each chromosomes. 5S and 45S rDNA sequences were located on two and three pairs of chromosomes, respectively. The centromere retrotransposon of Brassica (CRB) is a major component in Brassica related species that has been maintained as a common centromere component. CRB signals were detected on the centromere and pericentromeric region of R. sativus 'Wonkyo 10039' and three basic Brassica species (B. rapa, B. nigra, and B. oleracea). These results will provide a valuable background for physical mapping and elucidation of the evolutionary relationship among the Brassica related species.